STRATEGI PEMASARAN POLITIK PADA ERA DIGITAL: PEMANFAATAN INSTAGRAM DALAM KAMPANYE POLITIK PADA PILGUB DKI JAKARTA 2017 - Krisnanto, Indra Wahyu; ., Fitriyah (Journal of Politic and Government Studies, 2019)
The use of Instagram in political marketing strategies has become an important thing that cannot be ignored in the current digital era. Political marketing strategies begin to adopt sophisticated technology in its implementation. The existence of Instagram as a media campaign tries to overcome the weaknesses in conventional media. In order that every 2017 DKI Jakarta Gubernatorial Election candidate pairs together with his campaign team optimally uses Instagram to win political contestation.The research method used is a qualitative method. Namely in the form of a descriptive approach (explanatory) analytic with a comprehensive presentation of the results of interviews and observations and then analyzed in depth. The findings of this research are based on facts found in interviews and Instagram analysis as campaign media. Data collection through interviewing research informants, namely KPU Commissioner, Chairperson of Bawaslu, and all representatives of the campaign team from each candidates.The results of the study explain that Instagram has an important role in the 2017 DKI Jakarta Pilgub which is to reach out to first-time voters from the millennial generation (17-25 y.o.) and get public support from this audience segment. The way to package (framing) political messages in a political marketing strategy must also be adjusted to target the audience segment. In order that in packaging the content must contain important elements in it. In outline, the use of Instagram as a campaign media has two main contents, both contents that contain positive elements and content that contain negative elements. Instagram content in political campaigns that contain positive elements includes political marketing such as superior programs, interactions with the public, and political leadership figures. Whereas the Instagram content contains negative elements such as hoax issues and hate speech about the issue of SARA.Keywords: New Political Marketing Strategy, 2017 Jakarta Gubernatorial Election, Instagram as Media Campaign, Hate Speech and Political Hoax.